2017
DOI: 10.1080/03019233.2017.1410949
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bottom-blowing gas species on the nitrogen content in molten steel during the EAF steelmaking process

Abstract: In modern EAF steelmaking process, control of the nitrogen content of molten steel has become more and more important and bottom-blowing technique has been widely applied to promote the molten bath fluid flow, accelerate the metallurgical reaction and improve the quality of molten steel. In this study, the influence of bottom-blowing gas species on the nitrogen content in molten steel during EAF steelmaking was systematically investigated and analysed. Combining the induction furnace experiments and theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Anghelina et al [ 108 ] reported that due to high reaction rates, bubbles become saturated with nitrogen and there is no need to inject DRI fines too deep. Wei et al [ 55 ] compared the denitrogenization rate with argon and CO 2 . The higher‐stirring intensity using CO 2 decreased nitrogen to 12 ppm, in contrast to 34 ppm N using argon.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anghelina et al [ 108 ] reported that due to high reaction rates, bubbles become saturated with nitrogen and there is no need to inject DRI fines too deep. Wei et al [ 55 ] compared the denitrogenization rate with argon and CO 2 . The higher‐stirring intensity using CO 2 decreased nitrogen to 12 ppm, in contrast to 34 ppm N using argon.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…[ 57 ] CO 2 injection involves endothermic reactions with C and Fe contributing to a cooling effect around the porous plugs, improving the dephosphorization (DeP) rates and increasing the life of the porous plugs. Zhu et al [ 55 ] also reported higher decarburization rates using CO 2 because of its oxidizing nature. The concentration of nitrogen was lower injecting N 2 –CO 2 mixtures in comparison with Ar–N 2 mixtures.…”
Section: Bottom Gas Stirring In the Eafmentioning
confidence: 99%
See 1 more Smart Citation
“…Table I gives an overview of the applications of CO 2 in steelmaking processes and the results that have been obtained from the former research. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The theoretical basis for achieving the preceding effects is that CO 2 exhibits weak oxidation, which occurs through the reaction CO 2 + [C] = 2CO. The reaction characteristics mainly include the endothermic effect that reduces the temperature of the fire point zone and controls the heating rate of molten steel, generating nearly twice the amount of gas to improve the stirring intensity in the furnace, and selective oxidation of carbon and other valuable elements under different pressures and liquid steel compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [10] developed a computational fluid dynamics (CFD) model to analyse the effect of bottom-blowing arrangements on the EAF molten bath stirring. Wei [11,12] researched the effect of different bottom-blowing gas species on the molten bath stirring and the molten steel nitrogen content in EAF steelmaking. He [13] considered that bottom-blowing in EAF could promote mass transfer and accelerate the smelting rhythm to a certain extent.…”
Section: Introductionmentioning
confidence: 99%